Metode six sigma dalam pengendalian kualitas pada home industry tempe - Tri Lestari, Dian; Supardi, Supardi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Mr. Soyo's home industry tempe is a Small and Medium Enterprise (SME) engaged in the tempe food production industry. In the Mr. Soyo’s home industry temp. has problems in the production process, causing defects in the tempe products produced by 1.5%. The goal of this research is to analyze quality control in the home industry Tempe, as well as the amount-of faults that occur and the underlying variables. The six-sigma approach is used in conjunction with the DMAIC sequence (Define, Measure, Analyze, Improve, Control) to analyze secondary data from a production report from July to September 2021. Quality control in the home industry Tempe was good, according to the analysis of DPMO value (Defect Per Million Opportunity) which was 4,997 and sigma level 4.13, and the magnitude of the problem was within the boundaries of tolerance.  Kind defects caused during the production process are broken packaging, imperfect shape and flaccid texture.  The cause of the packaging is damaged and the shape is that fermentation rack in open and unclean areas, the causative factor of flaccid texture is that there is no yeast guide and no sign of leaven bought.